Early childhood food literacy in the family context: A literature review - NILAM KEMUNING HER PANULUH,; hapidin,; Elindra Yetti, (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Early childhood food literacy in the family context: A literature review Nilam Kemuning Her Panuluh, Hapidin dan Elindra Yetti Program Studi Magister Pendidikan Anak Usia Dini, Fakultas Ilmu Pendidikan, Universitas Negeri Jakarta. Univeritas Negeri Jakarta, Gedung A, Rawamangun, Jakarta Timur Email: nilam.kemuning.her@mhs.unj.ac.id nilamkemuning@gmail.com Abstract Food literacy is a person's competence in obtaining and understanding the basic concepts of food as a whole and in-depth (understanding, nutritional content, benefits, position, access, systems and the impact of food on health, the environment and the economy), skills in choosing, processing, managing food and positive attitudes towards food ingredients which are shown in behavior towards daily food ingredients confidently, responsibly and sustainably. Food literacy is a basic competency that needs to be instilled from an early age to form healthy and nutritious eating habits and responsible consumption behavior for optimal growth and development of children and a bright future for the nation. Family is the first environment that has a strategic role in shaping food literacy in early childhood. This study aims to examine the importance of food literacy in early childhood and the role of families in helping food literacy in early childhood. The method used is a literature review of books, guidelines, reports and articles in research journals relevant to the research objectives within the last 10 years. The results of the study show that food literacy is important to be instilled in early childhood and families have a strategic role in shaping food literacy through instilling values, understanding and habituation of family daily eating practices. The findings in this study recommend the need to strengthen the family approach in nutrition and food education and intervention programs in early childhood education to create a golden generation and a bright future for the nation. Keywords: food literacy, early childhood, family role, nutrition education, feeding practices and eating habits.